The Effect of Service Quality on Shopee Customer Satisfaction on Students of the Technology and Business Master Institute Pekanbaru - mohd winario; Muhammad Mardiansyah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2022)
This study aims to determine and analyze the effect of service quality on customer satisfaction. The analysis in this study uses the independent variable of service quality. The dependent variable is customer satisfaction. The sample of this research is the students of the Master's Institute. The sample is carried out using a non-probability sampling technique, which is sampling that does not provide equal opportunities or opportunities for each member of the population to be selected as a sample. Data collection techniques were carried out by means of questionnaires and interviews. The total population at the Master's Institute is 3004 and the sample obtained is 97 people. The results obtained that the t value is known to have a t-count of 7.920 > t-table 0.199, so it can be concluded that the service quality variable (X) has a significant effect on the consumer satisfaction variable (Y). The results obtained that the R2 value of the coefficient of determination is found in the Adjusted R Square of 0.391. This means that the ability of the independent variable to explain the dependent variable is 39.1%, the remaining 61.9% is explained by other variables not discussed in this study.